A moisture and electric coupling stimulated ionic polymer-metal composite actuator with controllable deformation behavior. (16th January 2018) - Ru, Jie; Zhu, Zicai; Wang, Yanjie; Chen, Hualing; Bian, Changsheng; Luo, Bin; Li, Dichen
Abstract: Ionic polymer-metal composite (IPMC) actuator can generate large and rapid deformation based on ion migration under a relatively low driving voltage. Under full hydrated conditions, the deformation is always prone to relaxation. At room humidity conditions, the deformation increases substantially at the early stage of actuation, and then decreases gradually. Generally, most researchers considered that the change of water content or relative humidity mainly leads to the deformation instabilities, which severely limits the practical applications of IPMC. In this Letter, a novel actuation mode is proposed to control the deformation behavior of IPMC by employing moisture as an independent or collaborative incentive source together with the electric field. The deformation response is continuously measured under electric field, electric field-moisture coupling stimulus and moisture stimulus. The result shows that moisture can be a favorable driving factor for IPMC actuation. Such an electric field-moisture coupling stimulus can avoid the occurrence of deformation instabilities and guarantee a superior controllable deformation in IPMC actuation. This research provides a new method to obtain stable and large deformation of IPMC, which is of great significance for the guidance of material design and application for IPMC and IPMC-type iEAP materials.